2001
DOI: 10.1051/kmae:2001012
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish Predation Experiments on the Introduced Zebra Mussel, Dreissena Polymorpha, in Ireland, and Their Potential for Biocontrol.

Abstract: The zebra mussel Dreissena polymorpha, native to the Aralo-Caspian region, has spread across Europe in the last 180 years. Although it reached England in 1820, it only arrived in Ireland in around 1995, probably attached to the hull of pleasure boats, and since then has spread through the lowland Shannon and Erne systems, which are linked by canal. While White-clawed crayfish Austropotamobius pallipes (Lereboullet) occur in these systems, Dreissena has not yet colonized sites with large crayfish populations. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Predation by an established crayfish population may confer a water body with resistance against zebra mussel invasion through predation of low numbers of small zebra mussel individuals (Reynolds & Donohoe, 2001). Conversely, if a zebra mussel population is established first, it may facilitate crayfish invasion by providing an abundant food source directly, as well as through providing habitat for other macroinvertebrate prey (Stewart et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Predation by an established crayfish population may confer a water body with resistance against zebra mussel invasion through predation of low numbers of small zebra mussel individuals (Reynolds & Donohoe, 2001). Conversely, if a zebra mussel population is established first, it may facilitate crayfish invasion by providing an abundant food source directly, as well as through providing habitat for other macroinvertebrate prey (Stewart et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Discrete size classes of mussels were used to facilitate statistical analysis of the data and identification of consumed mussels. The size classes selected are considerably larger than those used previously in experiments with other crayfish species (1-22 mm; Piesik, 1974;Love & Savino, 1993;MacIsaac, 1994;Martin & Corkum, 1994;Reynolds & Donohoe, 2001), but preliminary experiments and earlier study by Schreiber et al (1998) identified that signal crayfish are capable of consuming a greater range of mussel sizes.…”
Section: Prey Size Selectivitymentioning
confidence: 90%
See 1 more Smart Citation
“…1 week. In various studies, the starvation time considered varies between 24 hours and 9 days (Martin & Corkum 1994;Reynolds & Donohoe 2001;Mistri 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have investigated crayfish predation on zebra mussels (Piesik 1974;Love & Savino 1993;MacIsaac 1994;Martin & Corkum 1994;Perry et al 1997;Schreiber et al 1998;Reynolds & Donohoe 2001), including by Procambarus clarkii (Gonçalves 2013).…”
Section: Introductionmentioning
confidence: 99%